2021
DOI: 10.23937/2469-5858/1510114
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Treatment Practices of Medical Doctors towards Care of Elderly Patients Accessing Clinical Care at Hospitals in Kampala Uganda

Abstract: Background:The global trend towards an increasing aging population demands for adequate geriatric medical care services to cater for health needs of the aging population seeking clinical care in hospitals. In Uganda, geriatric care as a specialty in medicine is still at infancy stage, and this is further worsened by the fact that the current curricula followed in training health workers lacks a component dedicated to elderly care. There is therefore need to assess knowledge, attitudes and treatment practices o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Similar to this, application of practice by ICG, more than 74% of healthcare providers in Uganda do not frequently use the recommended care mode (Daniel et al, 2021). According to research from Slovakia, Bangladesh, and Uganda, inadequate knowledge was found to be substantially correlated with levels of training, education, and experience (Daniel et al, 2021;Mahmud et al, 2020). However, this is not adequate (Amsalu et al, 2021;Fita et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 69%
See 1 more Smart Citation
“…Similar to this, application of practice by ICG, more than 74% of healthcare providers in Uganda do not frequently use the recommended care mode (Daniel et al, 2021). According to research from Slovakia, Bangladesh, and Uganda, inadequate knowledge was found to be substantially correlated with levels of training, education, and experience (Daniel et al, 2021;Mahmud et al, 2020). However, this is not adequate (Amsalu et al, 2021;Fita et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 69%
“…According to 23% of research participants in a survey of 55 ICG in Belgium, the level of practice of PwD from inadequate to fair (Piers et al, 2019). Similar to this, application of practice by ICG, more than 74% of healthcare providers in Uganda do not frequently use the recommended care mode (Daniel et al, 2021). According to research from Slovakia, Bangladesh, and Uganda, inadequate knowledge was found to be substantially correlated with levels of training, education, and experience (Daniel et al, 2021;Mahmud et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 88%